Swarm Control for Managed Beehives - Sara DeBerry; John Crowley; James D. Ellis (EDIS)
Honey bee swarms are a normal sign of a productive and strong honey bee colony. The population of honey bees in the environment grows and genes are exchanged as the new queen in the parent colony mates with drones from other colonies in the surrounding environment. Unfortunately, this activity often conflicts with the goals of the beekeeper, so good colony management includes swarm prevention. During the swarm season, hive owners should undertake proactive beekeeping practices to alter colonies in response to potential swarming behavior. In this way, the beekeeper maintains strong colonies with greater honey production and the potential to split and increase the total number of colonies, all of which makes beekeeping much more profitable for hive owners.